Participation of women in public and political life: perspectives and obstacles - Antonina Ruds'ka (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
The article examines the relevance of the improvement of gender policy in Ukraine. Mechanisms of attracting women to assume leadership positions were analized. On the example of of Finland shown how women's participation in public life is ensured at the legislative level.
Keywords: gender; gender quotas; women